The phytological future of prostate cancer staging: PSMA-PET and the dandelion theory - Sathianathen, N; Geurts, N; Nair, R; Lawrentschuk, N; Murphy, D; Lamb, A (Future Medicine, 2017)
PSMA-PET is changing how we stage prostate cancer, both in the primary setting and with relapse after treatment. It allows us to identify lesions in the bones and lymph nodes that were not previously visible on conventional imaging with bone scan and CT/MRI. In this Special Report we review the 'state of the art' for PSMA imaging and discuss the implications for treatment decisions in prostate cancer. We liken early high risk or metastatic prostate to a common phytological problem: the dandelion. In this analogous situation, we consider the additional evidence needed for us to start plucking out the original dandelion and for us to focus attention on killing the seeded weeds that are identifiable elsewhere in the lawn.